PELATIHAN MODEL – MODEL PEMBELAJARAN PAIKEM BAGI MAHASISWA DAN GURU - Roswita Lioba Nahak; Selfiana Ndapa Lawa; Jhon Enstein; Vera Bulu; Maria Dosantos (Pengabdian Masyarakat Ilmu Pendidikan, 2022)
Tujuan dalam kegiatan ini untuk memberikan bekal pengetahuan kepada mahasiswa dan guru tentang model-model pembelajaran PAIKEM serta mampu modifikasi model pembelajaran, sehingga dapat diimplementasikan dalam kegiatan pembelajaran. Kegiatan dilakukan menggunakan zoom meeting. Pada kegiatan ini guru-guru dilatih dengan menggunakan pendekatan kolaboratif. Jumlah peserta sebanyak 66 peserta. Hasil kegiatan menujukkan respon baik, hal ini dibuktikan dari hasil survei menunjukkan 41,9% puas dan 58,1% sangat puas sebab tema yang diangkat sangat menarik dengan persentase sebesar 80,6% karena konten webinar yang edukatif, bermanfaat, menarik serta informatif. sehingga, secara umum penilaian peserta tentang pelatihan yang dilakukan sangat baik Kata Kunci : Pelatihan, Model Pembelajaran, PAIKEM Abstract The aims of doing this activity as one of the community services were to provide knowledge to students and teachers about PAIKEM (an Active, Innovative, Creative, Effective, and Exciting Learning) model and to be able to modify learning model, so that this learning model can be implemented in learning activities. The activity of community service was conducted using a zoom meeting. This community service provided an opportunity for teachers to be trained to use a collaborative approach. The number of participants was 66. The results of the activity showed a good response, this was proven by the survey results which showed 41.9% satisfied and 58.1% very satisfied. This meant that the theme taken was very interesting with a percentage of 80.6%, because the webinar content was educative, useful, interesting and informative. In general, the participants' assessments of the training carried out was very good. Key Words: Training, Learning Model, Active, Innovative, Creative, Effective, and Exciting Learning